2021
DOI: 10.1186/s41747-021-00210-8
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-aided CT segmentation for body composition analysis: a validation study

Abstract: Background Body composition is associated with survival outcome in oncological patients, but it is not routinely calculated. Manual segmentation of subcutaneous adipose tissue (SAT) and muscle is time-consuming and therefore limited to a single CT slice. Our goal was to develop an artificial-intelligence (AI)-based method for automated quantification of three-dimensional SAT and muscle volumes from CT images. Methods Ethical approvals from Gothenbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
1
27
0
2
Order By: Relevance
“…The main difference between these studies and the present one is the analysis of muscle volume compared to skeletal muscle area in a single axial cross-section at the level of the L3 vertebra. We have previously shown that these different measurements correlate, but that muscle volume has a lower variance and may therefore be a better and more reliable measure of sarcopenia [8]. The present study builds on that by showing that only very few CT studies could not be correctly analysed and that the association with OS holds true.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The main difference between these studies and the present one is the analysis of muscle volume compared to skeletal muscle area in a single axial cross-section at the level of the L3 vertebra. We have previously shown that these different measurements correlate, but that muscle volume has a lower variance and may therefore be a better and more reliable measure of sarcopenia [8]. The present study builds on that by showing that only very few CT studies could not be correctly analysed and that the association with OS holds true.…”
Section: Discussionmentioning
confidence: 57%
“…The AI-based tool consisted of a single convolutional neural network (CNN), that had previously been trained to segment muscle and fat [8]. In addition, the CNN had also previously been trained to detect and segment the sacrum and coccyx.…”
Section: Patients and Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed method of using ImageJ for the quantification of body compositions has been described previously [20]. Semi-automated segmentation was used during these manual courses by using tissuespecific attenuation thresholds such as skeletal muscle (− 29 to 150 HU) and adipose tissue (− 190 to − 30 HU) [21,22]. An example of segmented each type of tissue was shown in Additional file 1: Fig.…”
Section: Quantification Of Body Composition Parameters By Ctmentioning
confidence: 99%